The evolving low-cost business model: network implications of fare bundling and connecting flights in Europe - Fageda, Xavier; Suau-Sanchez, Pere; Mason, Keith J. (Elsevier, 2014)
In a context of limited organic growth, some low-cost airlines have considered business strategies that are changing two key principles of the low-cost airline business model: fare unbundling and point-to-point operations. Using a multivariate analysis we identify the influence of several route characteristics on the share that European pure low-cost and hybrid low-cost carriers have on the routes they operate. Results show that, from a network perspective, the distance between the archetypical low-cost carrier business model and the adapted low-cost carrier business model with a hybrid approach is widening. Differences are also clear between hybrids offering connecting services and hybrids offering fare bundling. The results are also important from an airport policy perspective, since secondary airports and legacy airports in transition could be able to reduce the gap between them and the main hub airports.
Keywords: Fare Unbundling